(untitled) (Journal of Surgical Sciences, 2019)
Mesenteric tumors are rare and consist of a heterogeneous group of lesions. Among them undifferentiatedcarcinoma of the mesentery is very rare entity. Here we present a case of undifferentiatedcarcinoma of the mesentery in a 51 year old male presented with rapidly increasing hugeabdominal lump,central abdominal pain and weight loss. Ultrasound of the whole abdomen andCT scan of whole abdomen reports were suggestive of retroperitoneal mass. The tumor wasresected and histopathology report was suggestive of malignant mesothelioma whereas immunohistochemistryreport revealed undifferentiated carcinoma of the mesentery. Journal of Surgical Sciences (2016) Vol. 20 (1) : 29-31